Trends in aircraft design - Newell, A. F.; Howe, D. (College of Aeronautics, 1962)
The improved performance of aircraft during the past decade has resulted in the need for new design and production techniques. Particular examples are integral construction and the use of sandwich panels. Although these processes are costly, especially when applied to titanium and steel construction, their use is likely to be necessary, at least to some extent. on many supersonic aircraft. The supersonic airliner is no exception to this and the paper discusses the design aspects of this type of aircraft which have a bearing on production problems. It is concluded that more research aimed at reducing the cost of sophisticated forms of construction is required.